Philippi, From Colonia Augusta to Communitas Christiana : Religion and Society in Transition - Friesen, Steven J.; Lychounas, Michalis; Schowalter, Daniel N. (Novum Testamentum, Supplements, 2022)
This volume provides a review of recent research in Philippi related to archaeology, demography, religion, the New Testament and early Christianity. Careful reading of texts, inscriptions, coins and other archaeological materials allow the reader to examine how religious practice in Philippi changed as the city moved from being a Hellenistic polis to a Roman colony to a center for Christian worship and pilgrimage. The essays raise questions about traditional understandings of material culture in Philippi, and come to conclusions that reflect more complicated and diverse views of the city and its inhabitants.